1999
DOI: 10.1002/(sici)1096-911x(199908)33:2<99::aid-mpo7>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Open‐label comparison of the antiemetic efficacy of single intravenous doses of dolasetron mesylate in pediatric cancer patients receiving moderately to highly emetogenic chemotherapy

Abstract: Background. Nausea and vomiting are among the most unpleasant adverse side effects of cancer therapy.Procedure. An open-label dose-escalation study was conducted to assess the appropriate intravenous dose of dolasetron for pediatric patients undergoing chemotherapy. Patients received dolasetron in single intravenous doses of 0.6 (n = 10), 1.2 (n = 12), 1.8 (n = 12), or 2.4 (n = 12) mg/kg 30 min before receiving emetogenic chemotherapy. Pharmacokinetic parameters were evaluated at each dose level and efficacy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Recently, Gupta et al [28] described prolongation of dispersion of QT and QTc intervals after anthracycline therapy for childhood malignancies even in the presence of normal QT and QTc intervals on ECG. Coppes et al [29] demonstrated asymptomatic increases at 1 hr posttreatment in the PR, QRS, QT, and QTc intervals in four different intravenous doses groups of dolasetron mesylate in children receiving chemotherapy. These increases were considered mild in intensity and without clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gupta et al [28] described prolongation of dispersion of QT and QTc intervals after anthracycline therapy for childhood malignancies even in the presence of normal QT and QTc intervals on ECG. Coppes et al [29] demonstrated asymptomatic increases at 1 hr posttreatment in the PR, QRS, QT, and QTc intervals in four different intravenous doses groups of dolasetron mesylate in children receiving chemotherapy. These increases were considered mild in intensity and without clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric population An open -label dose -escalation study by Coppes et al 28 evaluated four doses of iv dolasetron ( 0.6, 1.2, 1.8, 2.4 mg / kg ) in 46 pediatric patients ( 3± 18 years of age ) receiving moderately to highly emetogenic chemotherapy and experiencing acute emesis. The CR rates were 10% ( 1 of 10 ) , 25% ( 3 of 12 ) , 67% ( 8 of 12 ) , and 33% ( 4 of 12 ) , respectively.…”
Section: Dolasetron Use In Special Populationsmentioning
confidence: 99%